ANALISIS PEMASARAN HASIL PANEN UDANG VANAME DESA TEPPOE KECAMATAN POLEANG TIMUR KAB. BOMBANA - Irmawati, Irmawati; Madjid, Rahmat; Yusuf, Hayat; Kamaluddin, Murdjani; Putera, Asrip (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2021)
This study aims to determine the pattern of marketing channels, analyze costs, margins, and profits as well as the economic efficiency of each marketing channel for Vaname shrimp in Teppoe Village, Poleang Timur District. This research is a type of qualitative research with a descriptive approach. The types of data used in this study are qualitative data and quantitative data. Recording and observation data. The results of this study indicate that there are three patterns of shrimp marketing channels Vaname i.e., marketing channel I: Cultivators → Merchants Collector traders →Retailer Traders→Final Consumers, marketing channel II: Cultivators → Collector traders → Retailer traders →Final consumers, marketing channel III: Cultivators → Collector traders→Exporters. The total cost of marketing channel I is Rp. 1,550, marketing channel II is Rp. 2.250 and the total cost of marketing channel III is Rp.1.650. The marketing profit of marketing channel I is Rp. 6,450, the profit of marketing channel II is Rp. 5,750 and the profit of marketing channel III is Rp. 3,350. The marketing margin of marketing channel I is Rp. 8,000, marketing channel II is Rp. 8,000 and marketing channel III is 5,000. Farmer Share in marketing channel I is 88.5%, marketing channel II is 88.5% and marketing channel III is 92, 5%. Then for the most efficient marketing channel is the marketing channel I with the smallest efficiency value of 2.2%.